Essays on economic development and education - Delalibera, Bruno Ricardo (2018)
This thesis is a collection of three essays in economic development mainly focused on education. In the first two chapters, we study the effects that educational policies may have on a macroeconomic environment where individuals can invest in different stages of human capital formation. The last chapter introduces endogenous quality of teachers in human capital formation and measures the impact that the reallocation of talented workers toward this occupation may have on aggregate and regional GDP.